Evaluation of a school-based depression prevention program among adolescents with elevated depressive symptoms: study protocol of a randomized controlled trial. Issue 1 (December 2016) - de Jonge-Heesen, Karlijn; van Ettekoven, Kim; Rasing, Sanne; Liempd, Farina; Vermulst, Ad; Engels, Rutger; Creemers, Daan
Abstract Background Adolescents are at risk of developing depressive symptoms. Given the prevalence, recurrence and negative consequences of adolescent depression, it is crucial to implement prevention programs for high-risk adolescents. Prevention programs at an indicated level have shown to be successful in reducing depressive symptoms in adolescents. This study will evaluate the (cost)effectiveness of the prevention program 'Op Volle Kracht (OVK 2.0)' for adolescents with elevated depressive symptoms. Methods We will perform a Randomized Controlled Trial (RCT) with an intervention and control condition to test the effectiveness of an indicated prevention program aimed at depression in adolescents. Adolescents in their second year of secondary education (11–15 year) will be screened for depressive symptoms. Those with heightened levels of depressive symptoms (CDI-2 ≥ 14) will be randomly assigned to the intervention (N = 80) or control group (N = 80). The participants in the intervention condition will receive a prevention program comprising eight meetings of 60 min each. The participants in the control condition will receive psycho-educational information. All participants and their parents will complete assessment at baseline, post-intervention, and 6-, 12- and 24- month follow-up. Primary outcome will be depressive symptoms. Additionally, the present study will identify mechanisms that mediate and moderate the program effects and test the effect of OVK 2.0 on secondary outcomes. Discussion This paper describes a study designed to screen adolescents for depressive symptoms and offer them a prevention program to prevent the onset of depressive symptomatology. Adolescents in the intervention condition are expected to show lower levels of depressive symptoms at 12 month follow-up compared to adolescents in the control condition. If OVK 2.0 proves to be effective, the screening and intervention program could be implemented in schools on a large scale. Trial registration Dutch Trial RegisterNTR5725 . Date registered: 11th of March 2016.